MULTILINGUAL AND MONO-MULTILINGUAL STUDENTS’ PERFORMANCE IN ENGLISH SPEAKING - Bin-Tahir, Saidna Zulfiqar; Atmowardoyo, Haryanto; Dollah, Syarifuddin; Rinantanti, Yulini; Suriaman, Aminah (Study Program of English Literature, 2018)
The present study attempted to investigate and measure the performances of multilingual and mono-multilingual students of the pesantren modern IMMIM in Makassar. This study employed the mixed-method approach where the 30 students of the Junior High School were selected randomly and participated as the subject of the research. The qualitative data gained through the interview and observation of the students’ behavior in English speaking and the quantitative data obtained through the speaking test. The results show that the multilingual students tend to behave extrovert and ambivert behavior in English speaking while the mono-multilingual students behave introvert. It was strengthened by the speaking test achievement which shows that the multilingual students have the high score in terms of the fluency and comprehensibility while the mono-multilingual students have the high score regarding the accuracy, especially in grammar